A method for combined percutaneous and open surgical repair of Achilles tendon ruptures: A report of three cases - (:unkn) unknown (WILLIAMS & WILKINS, 1996)
Surgical treatment of Achilles tendon ruptures provides excellent functional results in active individuals, although it carries an incidence of wound complications. After experiencing a 25% wound complication rate with the traditional techniques in Achilles tendon ruptures, we modified the Bosworth technique by passing the gastrocsoleus flap percutaneously through the distal stump. This modification eliminated one third of the distal incision, which appears to be the most vulnerable part. We performed the operation in three consecutive cases. At 2-year follow-up there were no wound complications and no reruptures.
Keywords: CALCANEAL TENDON; SKIN; LEG